2017
DOI: 10.1186/s12906-017-1828-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Astragalus polysaccharides on attenuation of diabetic cardiomyopathy through inhibiting the extrinsic and intrinsic apoptotic pathways in high glucose -stimulated H9C2 cells

Abstract: BackgroundApoptosis plays a critical role in the progression of diabetic cardiomyopathy (DC). Astragalus polysaccharides (APS), an extract of astragalus membranaceus (AM), is an effective cardioprotectant. Currently, little is known about the detailed mechanisms underlying cardioprotective effects of APS. The aims of this study were to investigate the potential effects and mechanisms of APS on apoptosis employing a model of high glucose induction of apoptosis in H9C2 cells.MethodsA model of high glucose induct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…For instance, the specific polysaccharide receptor on the surface of muscle cells has yet to be identified. Because both β‐glucan and APS, which consists mainly of α‐(1→4), (1→6) dextran, arabinogalactan, rhanmnogalacturonan I, and arabinogalactan proteins (Sun et al, ), activated glucose uptake in muscle cells, this receptor probably recognizes a broad range of polysaccharides. Furthermore, it remains unclear for which enzyme phosphorylates AMPK in the L6 muscle cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the specific polysaccharide receptor on the surface of muscle cells has yet to be identified. Because both β‐glucan and APS, which consists mainly of α‐(1→4), (1→6) dextran, arabinogalactan, rhanmnogalacturonan I, and arabinogalactan proteins (Sun et al, ), activated glucose uptake in muscle cells, this receptor probably recognizes a broad range of polysaccharides. Furthermore, it remains unclear for which enzyme phosphorylates AMPK in the L6 muscle cells.…”
Section: Resultsmentioning
confidence: 99%
“…Laminarin S1-1 S1-2 S1-3 SG1-1 SG1-2 AS2-1-1 AS2-1-2 AS2-2 AS4-1 S1-1 S1-2 S1-3 SG1-1 AS2-1 AS2-1-2 AS2-2 AS3-1 AS4- (Sun et al, 2017), activated glucose uptake in muscle cells, this receptor probably recognizes a broad range of polysaccharides.…”
Section: Untreatedmentioning
confidence: 99%
“…In addition, our previous studies revealed that polysaccharides were the main active compounds of CV aqueous extract. Numerous studies have reported that polysaccharides protect against DCM by inhibiting oxidative stress or apoptosis or by activating heart chymase or the NRG1/ErbB pathway (Chang, Lu, Wang, Lv, & Fu, ; Chen et al, ; Sun et al, ). These findings suggest that CV extract has a functional role in protecting heart function in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is one of the major determining factors for the pathological progression of DM associated organ damages. Apoptosis causes cardiomyocyte loss thereby facilitating cardiac remodeling (Sun et al, ). The severity of diabetes is normally proportional to the levels of cardiac cell death (Ghosh et al, ) and attenuation of apoptosis has shown amelioration of diabetic cardiomyopathy (Tian et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in apoptosis event and associated downregulation of the protein mediators of apoptosis was correlated with suppression of TNF‐α. Accumulating evidences suggest that increase in the levels of pro‐inflammatory cytokine TNF‐α is one of the crucial events in DM associated cardiac apoptosis (Sun, Yang, Dai, Jia, Wang, Zhang & Mao, ; Westermann et al, ). VHVV considerably suppressed the markers of apoptosis such as cleaved caspase 3 and cytochrome c in H9c2 challenged with high glucose and elevated the expression of Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%